The role of melatonin in plant growth and metabolism, and its interplay with nitric oxide and auxin in plants under different types of abiotic stress - Ahmad, Irshad; Song, Xudong; Hussein Ibrahim, Muhi Eldeen; Jamal, Yousaf; Younas, Muhammad Usama; Zhu, Guanglong; Zhou, Guisheng; Adam Ali, Adam Yousif (Frontiers in Plant Science, 2023)
Melatonin is a pleiotropic signaling molecule that reduces the adverse effects of abiotic stresses and enhanced growth and physiology in many plant species. Several studies have recently demonstrated about the pivotal performance of melatonin in plants in regulating crop growth and yield. However, a comprehensive understating about melatonin, which regulates crop growth and yield under abiotic stress conditions is far from clear. This review focused on the research progresses on the biosynthesis, distribution, and metabolism of melatonin, and its multiple complex functions in plants and mechanisms of plant metabolism regulation under abiotic stresses. In this review, we not only focused the pivotal role of melatonin but also elucidated the interaction of melatonin with nitric oxide (NO) and auxin under abiotic stresses. The present review revealed that melatonin and its interaction with NO and auxin enhanced plant growth and yield under various abiotic stresses. The interaction of melatonin with NO regulated morpho-physiological and biochemical activities due to the G protein-coupled receptor and synthesis genes. The interaction of melatonin with auxin enhanced growth and physiology by increasing the levels of auxin, synthesis, and polar transport. Our aim is to provide a comprehensive review of the performance of melatonin under abiotic stresses, assisting in further interpretation of the mechanism that plant hormones use to regulate growth and yield under abiotic stresses.